ASSESMENT OF INFORMARTION SECURITY METHOD FROM OUTFLOW THROUGH TRANSIENT ELECTROMAGNETIC PULSE EMANATION - Хлапонін, Ю. І. (Science-based technologies, 2015)
Recently, methods of information interception with transient electromagnetic pulse emanation of local network elements are getting developed. Separate computers security methods are worked out well and backed up with necessary regulatory documents. However, information security through TEMPEST is far more hard to do in local network then in separate devices. That’s why special institutional, algorithmic and methodological approaches should be used to detect electromagnetic pulse emanations. Methods of spotting TEMPEST were analyzed. There are panoramas difference method, audiovisual method, expert method and parametric correlation method. Development of methodology for assessing information security from the information outflow by the transient electromagnetic pulse emanation of computer technology by using the text signal as a continuous sequence of pulses was the main goal of this project The mathematical apparatus allows calculating the energy of a single signal by transfer logic "1" or a logical "0".These approaches can be considered into accounting by improving special researches of transient electromagnetic pulse emanation methods on EVT.